Implementation of Performance Evaluation Through E-Kinerja BKN for Improving Apparatus Performance in Pohuwato Regency - Rolli Paramata, Moh.; Yakup, Yakup; R. Karundeng, Deby; Hunowu, Zet (LPPPIPublishing, 2024)
This study aims to analyze the implementation of performance evaluation through the E-Kinerja BKN application to improve the performance of government apparatus in Pohuwato Regency. The performance of government apparatus plays a crucial role in realizing optimal public services, in line with the vision of the Pohuwato Regency Medium-Term Development Plan (RPJMD) 2021-2026. This research employs a qualitative method with a descriptive approach to describe the implementation of performance evaluation and the challenges encountered. Data were collected through interviews and observations of government officials involved in the performance evaluation system. The findings indicate that the implementation of E-Kinerja enhances transparency and objectivity in employee performance assessment. However, several challenges remain, such as a lack of understanding among employees regarding the system, limited technological infrastructure, and resistance to transitioning from a manual to a digital system. Periodic evaluations reveal an improvement in employee effectiveness and productivity after the system's implementation. Therefore, increasing human resource capacity and strengthening technological infrastructure are necessary to ensure the successful implementation of E-Kinerja in enhancing the quality of government apparatus performance in Pohuwato Regency.